1986
DOI: 10.1002/ps.2780170605
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of the fungicide benomyl on posterior segmental regeneration in the earthworm, Eisenia fetida

Abstract: Earthworms, Eisenia fetida, were treated by surface exposure to the fungicide benomyl at various stages of posterior segmental regeneration. Teratogenic effects of benomyl were observed when worms were treated 7-11 days after amputation (i.e. during the normal period of segmental replication), but not during days 1-5,13-17, or 19-23. Teratogenic effects included a reduction in the number of regenerated segments, an increased frequency of segmental groove anomalies, and a variety of monstrosities. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A large number of studies have reported general histopathological changes such as bruising and swelling, especially in the clitellum region, tissue necrosis, and extrusion of coelomic fluid (Anton et al 1993;Aspock and An der Lan 1963;Cooper and Roch 1992;E1-Banhawy et al 1986;Gupta and Sundaraman 1988;Hans et al 1990;Karr et al 1990;Sileo and Gilman 1975;Stenersen 1979a;Stenersen et al 1975;Stokke and Stenersen 1993). In addition, Zoran et al (1986) observed teratogenic effects of benomyl in E. fetida under segmental regeneration. The effects have mainly been reported following exposure to organic pollutants, but such changes in earthworms have also been observed following exposure to heavy metal pollution (Gupta and Sundaraman 1990).…”
Section: Histopathological Responsesmentioning
confidence: 88%
See 1 more Smart Citation
“…A large number of studies have reported general histopathological changes such as bruising and swelling, especially in the clitellum region, tissue necrosis, and extrusion of coelomic fluid (Anton et al 1993;Aspock and An der Lan 1963;Cooper and Roch 1992;E1-Banhawy et al 1986;Gupta and Sundaraman 1988;Hans et al 1990;Karr et al 1990;Sileo and Gilman 1975;Stenersen 1979a;Stenersen et al 1975;Stokke and Stenersen 1993). In addition, Zoran et al (1986) observed teratogenic effects of benomyl in E. fetida under segmental regeneration. The effects have mainly been reported following exposure to organic pollutants, but such changes in earthworms have also been observed following exposure to heavy metal pollution (Gupta and Sundaraman 1990).…”
Section: Histopathological Responsesmentioning
confidence: 88%
“…For E. fetida, marked cellular enlargement followed by full depletion of the chloragogenous tissue took place under paraquat exposure (Fischer and Molnar 1992). Doseresponse relationships between the chemical exposure level and the histopatho- Karr et al (1990) Chloragogenous cell PblZn mine spoil D. rubidus Richards and Ireland (1978) Necrosis, loss of Carbofuran (Car) Not stated Sileo and Gilman movement (1975) Vogel and Seifert COONa, CaF2 (1992) Teratogenic effects Benomyl (Benz) E. fetida Zoran et al (1986) '(Car), carbamate; (Benz), benzimidazole; (OC), organochlorine; (OP), organophosphorus compounds.…”
Section: Histopathological Responsesmentioning
confidence: 97%
“…In many of the laboratory tests of toxicity, reported in the literature, the species used was not reported. When the species was reported it was usually L. terrestris (Heimbach 1985;Haque and Ebing 1983;Wentsel and Guelta 1987) A. caliginosa (Springett and Syers 1984;Martin 1986;EI Banhawy et al 1986) or E.fetida (Edwards 1983a;Roberts and Dorough 1984;Gestal van et al 1989;Neuhauser et al 1984;Hague and Ebing 1983;Inglesfield 1984;Bouwman and Reinecke 1987;Zoran et al 1986;Drewes et al 1987;Anton et al 1990;Leemput van et al 1989). However, some workers have used a wide range of species including Lampito mauritii Kinberg (Bharathi 1985;Bharathi and Subba Rao 1984) Pheretima posthuma Vaillant (Hans et al 1990) and Octochaetus pattom-6 (Abbasi and Soni 1983), Pheretima hUgendorji Michaelsen (Honda et al 1984).…”
Section: Variability In Toxicity O/chemicals To Different Earthworm Smentioning
confidence: 99%
“…Many workers have reported different types of malformations of earthworms in response to exposure to chemicals. For instance, the fungicide benomyl had teratogenic effects on the posterior segment regeneration of the earthworm E. fetida (Zoran et al 1986). These effects included an increased frequency of segmental groove anomalies and a variety of monstrosities, including two tails.…”
mentioning
confidence: 99%
“…Pesticides such as propoxur, methidathion, endosulfan, triazophos, carbofuran, terbufos and methomidophos cause such symptoms. Zoren et al (1986) reported the terratogenic effect of benomyl that is posterior segment regeneration of the earthworm, including an increased frequency of segmental groove anomalies and a variety of monstrosities, including two tails. Anton et al (1990) reported the occurrence of various malformation due to fungicide captan.…”
Section: Effect Of Pesticides On Earthwormsmentioning
confidence: 97%